Scapula fractures: a review. Issue 6 (28th June 2021) - Limb, David
Abstract : A consensus is beginning to emerge about the indications for fixation of fractures involving the glenoid fossa of the scapula. The same cannot be firmly said for extra-articular fractures of the blade or the processes of the scapula, with a good deal of reliance on expert opinion from high-volume centres. There are no randomized controlled studies and the systematic reviews that do exist can only pool the data from available case series, making meaningful meta-analysis of limited value. Interest in scapula fractures has increased of late due to the specific association of fractures of the scapular spine and acromion with reverse shoulder arthroplasty. This review summarizes the available evidence that can assist decision making when faced with a patient with a scapula fracture. Which patients should at least be considered for open reduction and internal fixation, either in the centre where they present or after referral to a more specialist centre? These patients are those with a fracture sufficiently displaced that it interferes with the mechanical function of the shoulder girdle and the aim of fixation is to reduce pain and disability. Since the majority of scapula fractures heal quickly with non-surgical treatment and do not cause significant disability, decision making can be difficult, and it is perhaps the case that it is easier to err on the side of caution. However, it seems that there are fracture types, such as significantly displaced double disruptions of the superior suspensory complex, widely displaced lateral column fractures and fractures producing angular deformity of the glenoid process, that benefit from early reduction and stabilization with the expectation of a good outcome for the patient. Cite this article: EFORT Open Rev 2021;6:518-525. DOI: 10.1302/2058-5241.6.210010